Proposed upgrading of kid's section in state library at Jalan Mahmood, 15200 Kota Bharu, Kelantan for Perbadanan Perpustakaan Awam Kelantan / Muhammad Imran Zainal Abidin - Zainal Abidin, Muhammad Imran (2012)
Final year student of Diploma Interior Architecture are required to completed every stage of their final design. This is to analysis towards student's knowledges about interior design from basic to the final presentation in board. Propose up-grading of Kids Library at Jalan Mahmood, 15200 Kota Bharu Kelantan for Perbadanan Perpustakaan Awam Kelantan, has been chosen for this final project. This is because, the client would like to upgrade and overcome the problems occur. Besides that, it also to attract and encourage the little kids to the Kids Library to the market. The concept and image that used for this art center must be reflect with client's needed and the theme of the Perpustakaan Perbadanan Awam Kelantan. Furthermore, through interviews, observation, media, internet and case study can be used to finish this project.